An Exploration of the Link between Development, Economic Growth, and Natural Risk - Hallegatte, Stephane (World Bank, Washington, DC, 2013)
This paper investigates the link between development, economic growth, and the economic losses from natural disasters in a general analytical framework, with an application to hurricane flood risks in New Orleans. It concludes that where capital accumulates through increased density of capital at risk in a given area, and the costs of protection therefore increase more slowly than capital at risk, (i) protection improves over time and the probability of disaster occurrence decreases; (ii) capital at risk -- and thus economic losses in case of disaster -- increases faster than economic growth; (iii) increased risk-taking reinforces economic growth. In this context, average annual losses from disasters grow with income, and they grow faster than income at low levels of development and slower than income at high levels of development. These findings are robust to a broad range of modeling choices and parameter values, and to the inclusion of risk aversion. They show that risk-taking is both a driver and a consequence of economic development, and that the world is very likely to experience fewer but more costly disasters in the future. It is therefore critical to increase economic resilience through the development of stronger recovery and reconstruction support instruments.